Recent advances in cell-laden 3D bioprinting: materials, technologies and applications. Issue 4 (October 2017) - Huang, Jie; Fu, Han; Li, Chong; Dai, Jianwu; Zhang, Zhijun
Fabrication of 3D scaffolds with patient-specific designs, high structural and component complexity, and rapid on-demand production at a low-cost by printing technique has attracted ever-increasing interests in tissue engineering. Cell-laden 3D bioprinting offers good prospects for future organ transplantation. Compared with nonbiological 3D printing, cell-laden 3D bioprinting involves more complex factors, including the choice of printing materials, the strategy of gelling, cell viability and technical challenges. Although cell-populated 3D bioprinting has so many complex factors, it has proven to be a useful and exciting tool with wide potential applications in regenerative medicine to generate a variety of transplantable tissues. In this review, we first overview the bioprinting materials, gelling strategies and some major applications of cell-laden 3D bioprinting, with main focus on the recent advances and current challenges of the field. Finally, we propose some future directions of the cell-populated 3D bioprinting in tissue engineering and regenerative medicine. In this review, we first overview the bioprinting materials, gelling strategies and some major applications of cell-populated 3D bioprinting, with main focus on the recent advances and current challenges of the field. Finally, we propose some future directions of the cell-laden 3D bioprinting in tissue engineering and regenerative medicine.